2013
DOI: 10.1007/s13205-013-0129-1
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of an extracellular laccase from solid-state culture of Pleurotus ostreatus HP-1

Abstract: A native isolate of Pleurotus ostreatus HP-1 (Genbank Accession No. EU420068) was found to have an excellent laccase producing ability. The extracellular laccase was purified to electrophoretic homogeneity from copper sulphate induced solid-state fermentation medium by ammonium sulphate precipitation and ion-exchange chromatography. The enzyme was determined to be monomeric protein with an apparent molecular mass of 68,420 kDa, and an isoelectric point (pI) of 3.5. The inductively coupled plasma spectroscopy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
56
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 41 publications
13
56
0
2
Order By: Relevance
“…The laccase from Xylaria sp. had an optimal reaction temperature between 50 and 60ºC (Fig.3b), which is similar to what was obtained for other reported fungal laccases (Forootanfar et al, 2011;Patel et al, 2014). The stability evaluated in the range from 4-70ºC showed that the laccase was mostly stable at temperatures below 30ºC but rapidly inactivated at temperatures of 40ºC and higher (Fig.3c); consistent results were obtained for the laccase of X. polymorpha (Liers et al, 2007), where the enzyme showed great stability at 20ºC for 4 hours but marked changes in residual activity at 40ºC and higher.…”
Section: Kinetic Properties Of Laccasesupporting
confidence: 88%
See 2 more Smart Citations
“…The laccase from Xylaria sp. had an optimal reaction temperature between 50 and 60ºC (Fig.3b), which is similar to what was obtained for other reported fungal laccases (Forootanfar et al, 2011;Patel et al, 2014). The stability evaluated in the range from 4-70ºC showed that the laccase was mostly stable at temperatures below 30ºC but rapidly inactivated at temperatures of 40ºC and higher (Fig.3c); consistent results were obtained for the laccase of X. polymorpha (Liers et al, 2007), where the enzyme showed great stability at 20ºC for 4 hours but marked changes in residual activity at 40ºC and higher.…”
Section: Kinetic Properties Of Laccasesupporting
confidence: 88%
“…These behaviors are interesting if is considered that one of the main features of the enzyme is that a metal is found on the active site. However, this behavior has also been found in other laccases (De-Souza and Peralta 2003;Patel et al, 2014), and it might be caused by the influence of the substrate on the inhibitory effect of EDTA. Lorenzo et al (2005) found that EDTA strongly inhibits the activity of enzymes when syringaldazine or 2,6-dimethoxyphenol are used as substrates, and when ABTS is used, EDTA did not behave as an efficient inhibitor.…”
Section: Effects Of Metal Ions and Chelating Agentsmentioning
confidence: 50%
See 1 more Smart Citation
“…No activity of laccase was measured from 65 °C upwards. This is similar as in articles 30,31 . For immobilized laccase on microparticles, activity decreased from 20 °C.…”
Section: Thermal Stabilitysupporting
confidence: 90%
“…Nonetheless, a higher affinity to ABTS is reported in comparison to other substrates such as syringaldazine or guaiacol among others, with lower oxidation velocity and higher K m values [4, 5, 35]. …”
Section: Discussionmentioning
confidence: 99%